2020
DOI: 10.1177/0021998320947136
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical behaviour and microscopic analysis of epoxy and E-glass reinforced banyan fibre composites with the application of artificial neural network and deep neural network for the automatic prediction of orientation

Abstract: This paper deals with the testing of tensile and flexural behaviour of epoxy-reinforced natural fibre composites, for which Banyan fibres have been selected as the natural fibre. Variations are made in the orientation of the fibres to determine which orientation made the composite the strongest. The fibre strands are arranged in different orientations, such as the uniaxial, biaxial and criss-cross arrangements, to differentiate between the orientations and observe which arrangement exhibited the best mechanica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Intricate details on crack propagation, the presence of defects and impurities, and the effect of additives on the components can be accessed using SEM. Figure 10 is a compilation of commonly observed microstructural features, with SEM images taken from the works of Shyam et al 1 Srinivasan et al 73 analysed the site of failure using SEM in the B and flax fibre composites. They inferred from the images that the adhesion between the fibres and the resin is strong as the fibres remain intact after crack propagation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intricate details on crack propagation, the presence of defects and impurities, and the effect of additives on the components can be accessed using SEM. Figure 10 is a compilation of commonly observed microstructural features, with SEM images taken from the works of Shyam et al 1 Srinivasan et al 73 analysed the site of failure using SEM in the B and flax fibre composites. They inferred from the images that the adhesion between the fibres and the resin is strong as the fibres remain intact after crack propagation.…”
Section: Discussionmentioning
confidence: 99%
“…A compilation of microstructural features observed from the SEM analysis done on banyan/E-glass NFCs by Shyam et al 1 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…e nine-node Lagrange element finite element model of laminated glass and the influence of boundary conditions, stacking sequence, glass size, collision speed, and impactor quality on the energy absorption characteristics of laminated glass at low speed are analyzed. Relevant scholars studied the influence of the failure threshold of laminated glass on the test results through a series of simulation experiments; the researchers used 3D solid elements to simulate windshield glass and studied its failure behavior under explosive load [12]. In the model, the glass layer adopts the principle of maximum principal stress to define the failure, and the PVB layer adopts the elastic-plastic and superelastic material model [13].…”
Section: Related Workmentioning
confidence: 99%
“…When a data set is well-trained by a neural network, it can be used to predict the output of some new input data sets. This technique was not used to model the sandwich panel properties to predict and determine the optimal point of properties; however, various studies were performed on other wood-based panels and showed that the developed ANN models could evaluate the properties of the wood composite products with a good precision [22][23][24].…”
Section: Introductionmentioning
confidence: 99%